2002
DOI: 10.2466/pms.2002.94.3c.1131
|View full text |Cite
|
Sign up to set email alerts
|

Modeling in Learning Two Volleyball Skills

Abstract: The present study was designed to investigate the influence of two different types of modeling and knowledge of performance on acquisition and retention of two volleyball skills (set and serve). Participants were 63 boys and 53 girls in elementary school, whose mean age was 11.7 yr. (SD=.5). The children were randomly assigned into two groups given the same practice method for 16 practice sessions (8 for the set and 8 for the serve) but different types of modeling. Some participants observed a videotape of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 29 publications
1
39
0
2
Order By: Relevance
“…Bandura's social learning theory states that observational learning is a process which leads to individual recognition of the skills and production of movement. Skill display allows the leaners to visually relate the oral description of the skill to information obtained from the valid tokens of the task for a successful performance (4). On the other hand, when someone sees a model, the pattern of skill will be learned with a focus on the spatial and temporal characteristics of that skill.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bandura's social learning theory states that observational learning is a process which leads to individual recognition of the skills and production of movement. Skill display allows the leaners to visually relate the oral description of the skill to information obtained from the valid tokens of the task for a successful performance (4). On the other hand, when someone sees a model, the pattern of skill will be learned with a focus on the spatial and temporal characteristics of that skill.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, when someone sees a model, the pattern of skill will be learned with a focus on the spatial and temporal characteristics of that skill. In order to develop the movement pattern, the observer perceives and uses the fixed (quintessential) aspects of movement coordination pattern (4). Arising from observational learning, neuromuscular effects theory confirms the effect of pairwise video feedback on learning of motion skills.…”
Section: Introductionmentioning
confidence: 94%
“…Estes estudos são desenvolvidos com tarefas utilizadas no dia a dia 3 , ou ainda com habilidades esportivas, e apesar de testarem resultados obtidos em estudos de laboratório, ainda não são caracterizados como pesquisa aplicada 4 . São encontrados estudos que testaram os efeitos da interferência contextual 5,3 , do "feedback" [6][7] , do estabelecimento de metas 8 e da demonstração [9][10] . Dentre estes fatores que afetam a aquisição de habilidades motoras, a demonstração tem recebido atenção ao longo dos anos, pois é uma forma de fornecer informação relacionada ao padrão espaço-temporal de uma ação a ser realizada para alcançar a meta da tarefa em questão 11 .…”
Section: Palavras-chave: Habilidade Motora; Aprendizagem Motora; Padrunclassified
“…With the advancement in rehabilitative technology, feedback such as biofeedback and/or visual feedback has been commonly used to facilitate learning [5][6][7][8][9]. Video demonstration and augmented feedback can provide knowledge of both movement (pattern) performance and movement results, and several studies have demonstrated the benefits of video feedback in individuals without SCI [10][11][12]. For example, videos have been widely used as a source of feedback for motor skill acquisition in sport performance [10,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%